STUDIES OF LINEAR POLYMER DIMENSIONS OF POLY(4-CHLOROSTYRENE) IN VARIOUS SOLVENTS AROUND THE THETA-TEMPERATURES BY INTRINSIC-VISCOSITY - BAYSAL, BM; YILMAZ, F (JOHN WILEY & SONS LTD, 1992)
Intrinsic viscosities of poly(4-chlorostyrene) solutions in isopropyl-benzene and n-propylbenzene at temperatures above and below the theta (theta) temperatures of these solvents were measured using a capillary viscometer. The viscosity measurements were performed on three poly(4-chlorostyrene) samples having molecular weights (M(v)BAR) 1.75 x 10(6), 6.5 x 10(5) and 2.7 x 10(5). A smooth and continuous contraction below the theta-temperatures was observed for both solvents. The temperature dependence of [eta] can be represented by a master curve in a plot of alpha(eta)3\tau\M1/2 (g1/2 mol-1/2) versus \tau\M1/2 (g1/2 mol-1/2), where alpha(eta) = [eta(T)]/[eta(theta)]1/3 is the expansion factor and tau = (T - theta)/T is the reduced temperature. A universal plot of reduced viscosity size (alpha(eta)) versus reduced blob parameter (N/N(c)) shows the achievement of collapsed state for T theta. The temperature dependence of intrinsic viscosity, both below and above the theta-temperature, exhibits similar behaviour to the temperature dependence of dipole moments for both of these solvents.
Keywords: POLYMER; COIL-GLOBULE; TRANSITION; COLLAPSE; THETA-TEMPERATURE; INTRINSIC VISCOSITY; PHASE-TRANSITION; HYDRODYNAMIC RADIUS; COLLAPSED REGIME; MOLECULAR-WEIGHT; DNA CONDENSATION; FLEXIBLE COILS; POLYSTYRENE; GELS; CYCLOHEXANE; DEPENDENCE; Polymer Science